2011
DOI: 10.1016/s1995-7645(11)60090-4
|View full text |Cite
|
Sign up to set email alerts
|

Status of carbohydrate, protein and lipid profile in the mosquito larvae treated with certain phytoextracts

Abstract: Two extracts produce significant alterations in the biochemical profiles of anopheline and culicine larvae. Further, the impacting factors of extracts on carbohydrate, lipid and protein contents of larvae are species and specific extraction. It indicates the disturbed metabolic activity of the larvae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 17 publications
5
22
0
Order By: Relevance
“…According to Sharma et al . (), the decrease in the protein levels in the P. nigrispinus nymphs caused by the botanical insecticide is probably due to the interference to the hormones that regulate protein synthesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Sharma et al . (), the decrease in the protein levels in the P. nigrispinus nymphs caused by the botanical insecticide is probably due to the interference to the hormones that regulate protein synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…According to Sharma et al (2011), the decrease in the protein levels in the P. nigrispinus nymphs caused by the botanical insecticide is probably due to the interference to the hormones that regulate protein synthesis. Therefore, the decrease in sugar and protein levels in the P. nigrispinus nymphs treated with azadirachtin shows that this insecticide is able to modify the biochemical profile of this predator.…”
Section: Discussionmentioning
confidence: 99%
“…The Artemisia annua extract negatively affects the growth and the development of C. quinquefasciatus (Sharma et al, 2011). Plant extracts tested against larvae, and adults of An.…”
Section: Discussionmentioning
confidence: 99%
“…However, changes in the synthesis of proteins and total lipids after the exposure of the larvae of C. quinquefasciatus to imidacloprid have been observed (Rao et al 2008). Moreover, it was observed a significant change in the biochemical profile of the larvae of Anopheles stephensi and C. quinquefasciatus exposed to certain phytoextracts (Sharma et al 2011).…”
Section: Introductionmentioning
confidence: 97%
“…Furthermore, the carbohydrate reduction may be due to prohibiting effects of the tested IGRs on glycogen and/or trehalose or interference with the glycolytic path-way. On the other hand, it is suggested that this carbohydrate depletion may be due to the utilization of the reserved glucose sources of the larval tissues as a result of IGRs' stresses (Sharma et al, 2011).…”
Section: Disturbed Carbohydrate Content In P Unionalis By Igrsmentioning
confidence: 99%